Cardiac implantable electronic device placement following alcohol septal ablation for hypertrophic cardiomyopathy in the United States. (27th July 2020) - Lam, Matthew C.; Naidu, Srihari S.; Kolte, Dhaval; Kennedy, Kevin; Feldman, Dmitriy N.; Chu, Antony F.; Abbott, J. Dawn; Gordon, Paul; Aronow, Herbert D.
Abstract: Background: Cardiac implantable electronic devices (CIED) are sometimes required after alcohol septal ablation (ASA) for hypertrophic cardiomyopathy (HCM). The primary objectives of this study were to characterize the incidence, timing, and predictors of CIED placement after ASA for HCM. Methods: Patients were identified from the 2010–2015 Nationwide Readmissions Databases. Incidence, timing and independent predictors of CIED placement, as well as 30‐day readmission rates were examined. Results: There were 1296 patients (national estimate = 2864) with HCM who underwent ASA. CIED were implanted in 322 (25% overall; 14% permanent pacemaker, 11% implantable cardioverter defibrillator) during the index hospitalization. Of these, 21%, 23%, 21%, and 18% occurred on postprocedure day 0, 1, 2, and 3, respectively. Only 17 (1.3%) patients underwent CIED implantation between discharge and 30‐day follow up. Independent predictors of index hospitalization CIED implantation included older age, diabetes, heart failure, nonelective index hospital admission and hospitalization at a privately owned hospital. Nonelective 30‐day readmission rates among those who did and did not undergo CIED placement during their index hospitalization, were 6.8% and 7.9%, respectively ( p = .53); median time to readmission was also similar between groups. Conclusions: One in four HCM patients undergoing ASA underwent CIED implantation during their index hospitalization; nearly 2/3rd during the first 48 h postprocedure. Private hospital ownership independently predicted CIED placement. More data are needed to better understand the unexpectedly high rates of CIED placement, earlier than anticipated timing of implantation and differential rates by hospital ownership.